Working and non-working mother's involvement in school and academic performance of their children in the elementary level (Journal of the Philippine Association for Technology in Home Economics in State Colleges and Universities, Inc., 2001)
The study was conducted to determine the extent of involvement of working and non-working mothers in school activities and academic performance of their children in the elementary level. It also determined if the mother's socio-demographic characteristics, the pupil related factors and the extent of involvement of mothers in school activities such as: co-teacher, volunteer, policy-maker, financier and spectator affect the academic performance of their children in the primary grades. Three hundred twenty mothers of elementary pupils in three public schools in Nueva Ecija participated. Results revealed that the academic performance of children of working and non-working mothers among the three participating schools is affected by the extent of involvement as co-teacher and some socio-demographic variables such as family income, number of children, educational attainment, availability of educational resources at home and pupil's gender. Results of the study further showed that the academic performance of the children of working mothers did not differ from the academic performance of the children of non-working mothers based on their grade average obtained during SY 1999-2000. Based on the results, mothers should not feel guilty to leave their children behind while they work since the study showed that there was no positive nor negative correlation of whether the mother works or not to the academic performance of their children. However, it could have an effect on the emotional quotient or EQ of the children.